Financial Capability in Colombia : Results from a National Survey on Financial Behaviors, Attitudes, and Knowledge - Reddy, Rekha; Bruhn, Miriam; Tan, Congyan (World Bank, Washington, DC, 2016)
Colombian authorities have made financial inclusion a core element of the country's socioeconomic development. The Central Bank of Colombia (BRC) requested support from the World Bank to develop and execute a nationally representative survey on financial capability. This report covers the first nationally representative study to detail the financial behavior, attitudes, and knowledge that comprise financial capability. One complementary national study is the annual Household Financial Burden and Education Survey (IEFIC) jointly undertaken by the BRC and the National Administrative Department of Statistics (DANE). This report provides insights on consumer behavior, attitudes, and knowledge relevant to initiatives promoting financial education and financial inclusion. Preliminary insights from this study have been used in developing the National Strategy on Social and Economic Policy (CONPES) document outlining the strategy for financial education in Colombia. There is an ongoing debate over measures that will codify a national financial education strategy into law. This report has following four objectives: (i) to provide empirical evidence on the financial behavior, attitudes, and knowledge of the Colombian population; (ii) to support the design of public policies to enhance both knowledge about and the quality of financial services; (iii) to highlight vulnerabilities and gaps in particular segments of the population with the goal of improving and focusing public policies and interventions where they are most needed; and (iv) to provide a basis for international comparison with other countries for which these data are available. This report describes a baseline measure of the financial capability of the Colombian adult population and highlights key results from the first national survey. This report is organized as follows: chapter one gives introduction. Chapter two describes key findings related to daily money management and financial planning behaviors and attitudes. Chapter three examines decisions related to the use of financial products and level of financial knowledge. Chapter four summarizes key behaviors and attitudes into financial capability scores, facilitating the creation of profiles and comparisons among different segments of the population. Chapter five presents international comparisons. Chapter six examines the relationship between financial capability, financial knowledge, and financial inclusion. Chapter seven provides policy recommendations related to the key challenges to financial capability identified in the report.